Szkolne kasy oszczędności w okresie międzywojennym (1918–1939) w kontekście działań władz oświatowych - Magiera, Elżbieta (Biuletyn Historii Wychowania, 2014)
The first school savings bank came into existence in Ghent, Belgium. It was founded by Francis Laurent in 1866. In Poland, the concept of saiving began to spread in the period of the National Education Commission, which recommended that children “practice thriftiness”. Since the beginning of the 19th century, local attempts to establish school savings banks were undertaken in the Polish lands that had been divided in the partitions. The propagation of thrift developed on a broader scale only after regaining independence, especially after the economic reforms of 1924. The Ministry of Education recommended that teachers introduce various forms of thrift: organising school savings banks, talks and lectures about saving, celebration of Savings Day and promoting the idea in society as a whole. The interest in the propagation of thrift in education was expressed by the central and local education authorities by issuing various types of legal acts on this subject. The intensive development of school savings banks started in 1925. Until 1935, these organisations operated on cooperative principles. After 1935 they were held under the auspices of the Postal Savings Bank, which was dissolved in 1947. The state-owned Common Savings Bank was created in its place, whose supervision of school savings banks continues to this day and is a statutory duty of the bank. Thus, the interwar experience in the field of organising school savings banks was continued after the Second World War and is still being implemented in the contemporary educational reality.